Student’s Mathematical Problem Solving Skills and Self-Efficacy on Word Problems through Technology-Based Learning - Nandang Arif Saefuloh; Mohamad Gilar Jatisunda; Mardiyah Syofiana; Yanti Mulyanti (RANGE: Jurnal Pendidikan Matematika, 2026)
Students’ ability to solve mathematical word problems is closely linked to their mathematical problem-solving skills and self-efficacy. This study examines the influence of two technology-based learning approaches—synchronous learning (via Zoom and Google Meet) and asynchronous learning (via WhatsApp)—on students' problem-solving performance and self-efficacy levels. The research involved 27 seventh-grade students in Bandung and employed a mixed-method design with an explanatory sequential approach. The findings revealed a strong relationship between the type of technology-mediated learning and students’ self-efficacy in mathematical problem solving. Students who engaged in synchronous learning demonstrated better performance in interpreting problems, developing strategies, and justifying solutions compared to those who used asynchronous methods. Learners with moderate to high self- efficacy consistently outperformed those with low self-efficacy, particularly in identifying relevant information, making conjectures, and generalizing patterns. In contrast, students with low self-efficacy showed difficulties in solving word problems and exhibited limited use of key processes in problem solving. These results emphasize the importance of aligning instructional approaches with students' self-efficacy levels and providing structured support for students involved in asynchronous learning to strengthen their mathematical problem-solving abilities.